Upaya Penanganan Demam Tifoid pada Kehamilan - Afiqah Divaulhaq; Annisa Uljannah (Lembaga Pengembangan Kinerja Dosen, 2026)
Typhoid fever during pregnancy can lead to complications such as uteroplacental infection, miscarriage, and vertical transmission, which causes neonatal typhoid. Typhoid fever is found worldwide and is highly prevalent in developing countries, particularly in tropical regions. It is estimated that there are 11–21 million cases per year and approximately 128,000–161,000 deaths per year; the majority of cases occur in Southeast Asia, South Asia, and Sub-Saharan Africa. Salmonella typhi is a gram-negative bacterium capable of intracellular survival. Symptoms in typhoid patients vary among different groups. While pregnant women with typhoid are more likely to exhibit coughing, non-pregnant patients more frequently report nausea/vomiting compared to pregnant patients. The effects of typhoid fever on pregnancy result from prolonged high fever and poor general health, which can lead to miscarriage, preterm labor, and intrauterine fetal death, especially if the infection occurs during the first or second trimester. Morbidity and mortality rates may be higher in pregnant women. Pregnancy itself does not affect the course of the disease. Prevention of typhoid fever involves adopting a clean and healthy lifestyle, as well as receiving the typhoid vaccine. Two effective vaccines are available for typhoid fever. The live-attenuated oral vaccine (Ty21a) requires four doses, administered 48 hours apart, without concurrent use of antibiotics or antimicrobial medications. Due to reduced gastrointestinal motility in early pregnancy and frequent nausea and vomiting associated with symptomatic gastroesophageal reflux requiring acid-reducing therapy, we do not recommend the Ty21a oral vaccine for pregnant patients.